GROUNDWATER VULNERABILITY MAPPING AND CONTAMINATION RISKS AT PONTAL DO PARANAPANEMA REGION (UGRHI - 22) - Romagnoli, I.; Manzione, R. L. (Revista Brasileira de Engenharia de Biossistemas, 2018)
Among the main risks that agro-business brings to the region of Pontal do Paranapanema (SP) are those related to the indiscriminate use of pesticides. The use of pesticides combined with improper handling can lead to contamination of groundwater and consequently to harmful effects on human and environmental health. Pontal do Paranapanema (SP) has a recent expansion of the sugarcane crop, begun in the year 2000. It is covered by sediments of the Bauru aquifer, and the whole region can be considered as naturally vulnerable, since it is an aquifer with direct recharge. Therefore, the objective of this work was to evaluate the natural vulnerability of the Bauru Aquifer from the GOD method and to estimate groundwater contamination by pesticides used in sugarcane production from the ARAquá software, verifying the potential of contamination in Pontal do Paranapanema. The results showed that, despite a crop expansion of more than 1,000% in planted area, the high vulnerability class was the one that presented the least advance of the sugarcane cultivation area. Regarding the simulations carried out, it was possible to conclude that there were no active ingredient concentrations estimated above the value for the potability standard in the region. The most toxic pesticide with the highest values ​​of concentration in the estimates was Tebuthiuron, presenting a risk to aquatic plants and animals at risk of extinction.